METERED DOSE INHALATION FORMULATIONS OF SALBUTAMOL SULPHATE USING NON-CFC PROPELLANT TETRAFLUOROETHANE (International Journal of Pharmaceutical Sciences and Drug Research, 2011)
Salbutamol sulphate metered dose inhaler formulations were developed with chlorine free, non-CFC propellant Tetrafluoroethane. Suspension formulations were prepared with 4 mg of oleic acid as the surfactant and varying proportions of ethanol as the co-solvent. Developed formulations were subjected to various qualitative and quantitative tests to ensure proper stability of the final package. In-vitro drug deposition studies using Twin impinger and Anderson cascade impactor indicated a net respirable fraction of 34-36.7% for the optimized formulation. Stability studies showed that the formulation was stable for a period of three months under all storage conditions. Effects of different adaptors and metering valve designs on the performance of the formulation were also checked. Comparison of optimized formulation with commercial CFC and non-CFC formulations exhibited equivalent performance characteristics. Thus, Tetrafluoroethane proved to be an environment friendly substitute for CFC propellants in metered dose inhalation formulations.